Association of Peripheral Blood Biomarkers With Response to Anti-PD-1 Immunotherapy for Patients With Deficient Mismatch Repair Metastatic Colorectal Cancer: A Multicenter Cohort Study - Cheng, Yi-Kan; Chen, Dong-Wen; Chen, Ping; He, Xiaosheng; Li, Pei-Si; Lin, Zhen-Sen; Chen, Shao-Xia; Ye, Shu-Biao; Lan, Ping (Frontiers in Immunology, 2022)
Purpose Deficient mismatch repair (dMMR) is an established biomarker for the response to the programmed cell death (PD)-1 inhibitors in metastatic colorectal cancer (mCRC). Although patients with dMMR mCRC could achieve a high incidence of disease control and favorable progression-free survival (PFS), reported response rates to PD-1 inhibitors are variable from 28% to 52%. We aimed to explore the additional predictive biomarkers associated with response to anti-PD-1 immunotherapy in patients with dMMR mCRC. Methods This multicenter cohort study enrolled patients with dMMR mCRC receiving anti-PD-1 immunotherapy at the Sixth Affiliated Hospital of Sun Yat-sen University and Sun Yat-sen University Cancer Center between December 2016 and December 2019. The total information of 20 peripheral blood biomarkers, including T cells (frequency of CD4+ T cell, frequency of CD8+ T cell, and ratio of CD4+/CD8+), carcinoembryonic antigen (CEA), inflammatory markers, and lipid metabolism markers, was collected. The association between response or survival and peripheral blood parameters was analyzed. Results Among the tested parameters, the ratio of CD4+/CD8+ and frequency of CD4+ T cell were significantly associated with PFS (p = 0.023, p = 0.012) and overall survival (OS; p = 0.027, p = 0.019) in a univariate analysis. A lower level of CD4+/CD8+ ratio or frequency of CD4+ T cell showed a significant association with better overall response rates (ORRs; p = 0.03, p = 0.01). The ratio of CD4+/CD8+ and frequency of CD4+ T cell maintained significance in multivariate Cox model for PFS (HR = 9.23, p = 0.004; HR = 4.83, p = 0.02) and OS (HR = 15.22, p = 0.009; HR = 16.21, p = 0.025). Conclusion This study indicated that the ratio of CD4+/CD8+ and the frequency of CD4+ T cell might be crucial independent biomarkers within dMMR mCRC to better identify patients for anti-PD-1 immunotherapy. If validated in prospective clinical trials, the ratio of CD4+/CD8+ and the frequency of CD4+ T cell might aid in guiding the treatment of PD-1 inhibitors among patients with dMMR mCRC.